PUBLIC-PRIVATE PARTNERSHIPS AS A TOOL FOR DEVELOPING THE TOURISM INDUSTRY - Sаidmurоdоv Fеruz Sоdiqjоn о’gli (Journal of new century innovations, 2023)
Abstract: The article analyzes the world experience of using the mechanism of public-private partnership (PPP) in tourism, identifies the problems of its development in the Russian tourism industry.